A cross‐sectional study of immune seroconversion to SARS‐CoV‐2 in frontline maternity health professionals. (10th August 2020) - Bampoe, S.; Lucas, D. N.; Neall, G.; Sceales, P.; Aggarwal, R.; Caulfield, K.; Siassakos, D.; Odor, P. M.
Summary: COVID‐19, the respiratory disease caused by SARS‐CoV‐2, is thought to cause a milder illness in pregnancy with a greater proportion of asymptomatic carriers. This has important implications for the risk of patient‐to‐staff, staff‐to‐staff and staff‐to‐patient transmission among health professionals in maternity units. The aim of this study was to investigate the prevalence of previously undiagnosed SARS‐CoV‐2 infection in health professionals from two tertiary‐level maternity units in London, UK, and to determine associations between healthcare workers' characteristics, reported symptoms and serological evidence of prior SARS‐CoV‐2 infection. In total, 200 anaesthetists, midwives and obstetricians, with no previously confirmed diagnosis of COVID‐19, were tested for immune seroconversion using laboratory IgG assays. Comprehensive symptom and medical histories were also collected. Five out of 40 (12.5%; 95%CI 4.2–26.8%) anaesthetists, 7/52 (13.5%; 95%CI 5.6–25.8%) obstetricians and 17/108 (15.7%; 95%CI 9.5–24.0%) midwives were seropositive, with an overall total of 29/200 (14.5%; 95%CI 9.9–20.1%) of maternity healthcare workers testing positive for IgG antibodies against SARS‐CoV‐2. Of those who had seroconverted, 10/29 (35.5%) were completely asymptomatic. Fever or cough were only present in 6/29 (21%) and 10/29 (35%) respectively. Anosmia was the most common symptom occurring in 15/29 (52%) seropositive participants and was the only symptom that was predictive of positive seroconversion (OR 18; 95%CI 6–55). Of those who were seropositive, 59% had not self‐isolated at any point and continued to provide patient care in the hospital setting. This is the largest study of baseline immune seroconversion in maternity healthcare workers conducted to date and reveals that one out of six were seropositive, of whom one out of three were asymptomatic. This has significant implications for the risk of occupational transmission of SARS‐CoV‐2 for both staff and patients in maternity units. Regular testing of staff, including asymptomatic staff should be considered to reduce transmission risk.